Small victories : spotting improbable moments of grace - Lamott, Anne (New York : Riverhead Books, a member of Penguin Group (USA), 2014)
"From the bestselling author of Stitches and Help, Thanks, Wow comes her long-awaited collection of new and selected essays on hope, joy, and grace. Anne Lamott writes about faith, family, and community in essays that are both wise and irreverent. It's an approach that has become her trademark. Now in Small Victories, Lamott offers a new message of hope that celebrates the triumph of light over the darkness in our lives. Our victories over hardship and pain may seem small, she writes, but they change us-our perceptions, our perspectives, and our lives. Lamott writes of forgiveness, restoration, and transformation, how we can turn toward love even in the most hopeless situations, how we find the joy in getting lost and our amazement in finally being found. Profound and hilarious, honest and unexpected, the stories in Small Victories are proof that the human spirit is irrepressible. "--
"Anne Lamott writes about community, family and faith in essays that are wise, irreverent, funny and poignant - a style that has become her trademark. Now in Small Victories, Lamott has once again written a brilliant and insightful book that offers a message of hope that celebrates the triumph of light over the darkness in our lives. Our victories over hardships and pain may be small, they may be infrequent, but they keep us going and they often come from the most unexpected places: within ourselves. Lamott shows how we can forgive thoughtless family members; spotlights the value of turning toward love even in the most hopeless situations (the death of a loved one, a cancer diagnosis), and shows how to find the joy in getting lost in traffic while racing to the aid of a sick friend. Insightful and irreverent, the stories in Small Victories are proof that the human spirit is resilient and irrepressible"--
Keywords: Lamott, Anne -- Religion; Spiritual life; Grace; Hope; Joy; Life -- Religious aspects -- Christianity; Novelists, American -- 20th century -- Biography; Christian biography -- United States; LITERARY COLLECTIONS / Essays; RELIGION / Essays; RELIGION / Spirituality